Deep Pluralism in Indonesian Foreign Policy Under The Joko Widodo Administration - Tia Panca Rahmadhani; Wawan Budi Darmawan; Arfin Sudirman (Administratio, 2024)
Deep pluralism is used to describe post-colonial global society. At this point, power, wealth, cultural and political authority are widely distributed in a system that is highly interactive and interdependent. This concept has empirical and normative value for understanding Indonesian foreign policy. Empirically, this concept can help explain that Southern countries are the main drivers in the use of deep pluralism in modern history. While normatively, this concept helps to understand Indonesia's role in consensual and contested forms of deep pluralism. Using system dynamics, this article examines how deep pluralism is applied to Indonesia's foreign policy patterns under the Joko Widodo administration. It concludes that Indonesia has a policy pattern that tends towards a consensual form of deep pluralism in the spirit of raison de system.